A critical review on global trends in biogas scenario with its up-gradation techniques for fuel cell and future perspectives. (5th May 2021) - Thiruselvi, Devaraj; Kumar, Ponnusamy Senthil; Kumar, Madhava Anil; Lay, Chyi-How; Aathika, Salma; Mani, Yuvarani; Jagadiswary, D.; Dhanasekaran, Anuradha; Shanmugam, Palaniyandi; Sivanesan, Subramanian; Show, Pau-Loke
Abstract: Renewable biogas production technology is an excellent method for eradication of greenhouse gas emission and thereby reducing global warming. This review discusses extensively on global biomass potential, energy need and method of satisfying the energy demand through sustainable techniques. One of the best alternative technological developments for the conversion of waste into useful energy is anaerobic digestion to produce biogas. It is recognized as one among leading green energy to manage the environmental and meet the current energy tasks to tackle globally. Generally, biogas can be utilized for cooking, heat and electricity generation. In order to extend the scope of application, traces of carbon dioxide, hydrogen sulphide has to be removed by several upgrading technologies to produce high purity methane (90%). This study discusses on biogas up-gradation using physical and chemical absorption, membrane separation, cryogenic separation, hybrid technology etc. Among the various up-gradation techniques, hybrid technology yields methane purity of 97%. In addition, this work reviews about benefits and problems in anaerobic integrated Solid Oxide Fuel Cell (SOFC) with latest real-world achievement in SOFC. Several SOFC systems with dynamic model development were reviewed based on efficiency of power generation. SOFC generates 45% more electricity than generator with heat engine. This review extends the scope for further research in biogas upgradation and global warming mitigation potential with carbon credits. Graphical abstract: Image 1 Highlights: Waste to energy is the sustainable methodology to have unpolluted earth. Biomass is found as best renewable source of energy for CH4 production. Comparing with other upgrading methods, hybrid technology yields 97% pure CH4 . Upgraded biogas with >95% CH4 content increased SOFC efficiency. Gradual increase in global electricity production due to renewable sources.